The effectiveness of using the Lattice in multiplication skills among Year 5 in SK Beradek / Muhamad Shaharudin Muhamad Sarip - Muhamad Sarip, Muhamad Shaharudin (2015)
This research focuses on efforts to help improve the skills of multiplication by using Lattice method among the pupils in Year 5 at SK Beradek. The study involved 20 respondents were selected based on preliminary observations made in the class during the process of teaching and learning. This study was conducted based on Kurt Lewin's research model involves five main steps of identifying aspects of practice, designing an action plan, implementing the plan of action, the effect of the action, and reflection on all the action. Through the research instruments were implemented, researchers have identified several issues that affect pupils weaknesses in multiplying skills. Throughout the interviews and document analysis of diagnostic tests researchers has identified three problems or weaknesses faced by the pupils in solving the multiply questions. The problems are the pupils not memorized the multiplication tables, error in terms of algorithms, especially involving multiplication of whole numbers with two-digit numbers and errors involving regrouping the product of the multiplication. In accordance with it, Lattice method was introduced to help improve students' multiplication skills while avoiding misconceptions faced by students in multiplication skills. The implementation of this study appear to have yielded positive results and encouraging, this can be seen in terms of the mean or average test scores, the increase was 39.95% in progressive test compared diagnostic test of 42.05% to 82%. Many pupils also gave a positive response to the survey was conducted. So with this it can be proved that the Lattice method was introduced to the pupils in Year 5 can help them improve their skills and avoid algorithm mistakes in multiplication, especially for the questions multiply whole numbers by one-digit numbers.